Limited role of continental arc in crustal growth: Insights from zircon U-Pb ages and Lu-Hf isotopes of late Paleozoic granitoid plutons from the northern North China Craton - Jing Ran; Hao Wang; Jin-Hui Yang; Jin-Feng Sun; Jing-Yuan Chen; Yu-Sheng Zhu (Lithos, 2026)

Climate value of energy storage for floating photovoltaic across China’s decarbonizing power grids - Ran Hao; Xin Sun; Yuchen Zhao; Chengchao Huang; Lili Yang; Weiqiao Wang; Junyu Sun; Li Fei; Lihao Zhao (ENGINEERING Environment, 2026)

Multi-site Ag-π conductive gel for ultrasensitive digital acousto-optic sensor - Jintao Tian; Yihao He; Hao-Ran Yang; Xing Han; Xiao-Wen Sun; Hong Yao; Tai-Bao Wei; Jin-Fa Chen; Bingbing Shi; Qi Lin (Chemical Engineering Journal, 2026)

Effects of wastewater flow direction on sulfur-based autotrophic denitrification processes: operational patterns, denitrification performance and response mechanisms - Daheng Ren; Heng Dong; Wenke He; Zhiqiang Zuo; Xiangli Zeng; Xuchen Ba; Yang Yu; Haoran Xu; Guijiao Zhang; Ran Zeng; Jiamin Xu; Na Zhang; et al. (Chemical Engineering Journal, 2026)

Synthesis of hierarchically micro-mesoporous carbon nanospheres: Molecular insight into the role of hexamethylenetetramine on the pore architecture - Ran Yuan; Shuxia Yuan; Yu Yang; Chunxiang Lu; Guohua Sun; Shijie Wu; Xiaodan Ren; Hao Cui (Chemical Engineering Journal, 2026)

Direct synthesis of non-migratory, intrinsically antioxidant ultra-high molecular weight polyethylene by nickel catalysis - Fei-Ran Yang; Wen-Bing Wang; Tian-Ming Yang; Hao-Xiang Sun; Quan Wang; Meng-He Xu; Jia-Wei Chen; Chen Zou (Chemical Engineering Journal, 2026)

Algal community composition drives lake greenhouse gas emissions via dissolved organic matter transformation and microbial processing - Weiqiao Wang; Xin Sun; Ran Hao; Fei Li (Journal of Environmental Management, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Multiple magmatic episodes and metamorphic overprinting in the Archean Anshan Complex: Integrated zircon–rutile–titanite–apatite U–Pb geochronology and trace-element constraints - Qing-Feng Mei; Jin-Hui Yang; Jin-Feng Sun; Lei Xu; Jing Ran; Bao-Quan Zhou; Ya-Dong Wu; Hao Wang (Lithos, 2026)

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Unlocking the effects of cold plasma on enhancing the stabilization of oat flour: Insights from storage characteristics, lipidomics, and flavor analysis - Shunzhang Ma; Hao Ran; Jinquan Lin; Yuanlin Sun; Lizhen Zhang; Fang Zhong; Sumei Zhou; Dianzhi Hou (Journal of Stored Products Research, 2026)

Multi-omics analysis provides genetic evidence for the involvement of cell adhesion pathway in the pathogenesis of biliary atresia - Rui Dong; Jinhang Zhu; Chunjing Ye; Fenglong Sun; Cong Huai; Wei Zhou; Jiajie Zhu; Xiaoqi Feng; Qiange Xiao; Deqian Chen; Yifan Yang; Ran Yang; et al. (Science China Life Sciences, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Antibacterial effect of the endolysin LysMD10 combined with citric acid against Salmonella and its application for eggshells decontamination - Hao Ding; Kaiyuan Huang; Tao Wang; Junjie Xu; Lichang Sun; Xinyi Zhang; Jiayuan Du; Xinxin Yang; Pengfei Gao; Bowen Liu; Hongduo Bao; Ran Wang; et al. (Food Control, 2026)

Competitive nitrogen/phosphorus scarcity triggers multi-pathway nitrogen removal and phosphorus-stress response in microalgae-bacterial symbiosis: poly-metabolic synergy enhancement mechanisms - Lili Yang; Wenqian Wei; Xin Sun; Xiang Li; Xiaowen Wen; Binchen Mao; Ran Hao; Weihan Qiu; Huipeng Li (Bioresource Technology, 2026)

Integrative analysis of DEHP exposure and prostate cancer: Mechanistic insights and predictive modeling - Wen-Cai Zheng; Wen-Tao Xu; Chao-Ran Chen; Fei Lin; Shao-Hao Chen; Xiao-Dong Li; Xiong-Lin Sun; Qing-Shui Zheng; Yong Wei; Xue-Yi Xue; Zhi-Bin Ke; Ning Xu (Environmental Pollution, 2026)

A knowledge map-based review of GRACE satellite applications across multiple domains: challenges and future directions - Junyu Sun; Xin Sun; Riquan Song; Ran Hao; Hongwei Li (Acta Geophysica, 2026)

Contribution of lakes to global greenhouse gas emissions: Mechanisms, quantification and mitigation strategies - Weiqiao Wang; Xin Sun; Xue Zhu; Ran Hao; Fei Li (Journal of Environmental Management, 2026)

Liquid-like PDMS brushes/TiO2 microcapsule-driven coatings with integrated self-healing, photodegradation, and antifouling functions - Jingjing Ren; Taolin Zhang; Shouzheng Jiao; Fanghua Pan; Jingru Sun; Ran Mo; Yuwei Hao; Zhengyu Chen; Siqiao Zhang; Zhicheng Sun; Zhongjun Cheng (Journal of Environmental Chemical Engineering, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Unveiling the differences between vitexin and isovitexin: From the perspective of sources, green advanced extraction technologies, biological activities, and safety - Jinquan Lin; Hao Ran; Qiqian Feng; Qun Shen; Sumei Zhou; Yuanlin Sun; Dianzhi Hou (Food Chemistry, 2025)

New insights into microalgal-bacterial immobilization systems for wastewater treatment: mechanisms, enhancement strategies, and application prospects - Lili Yang; Xin Sun; Hongwei Li; Ran Hao; Fengling Liu (Bioresource Technology, 2025)

Integrating allocation methods and regional optimization in life cycle assessment of floating photovoltaics for cleaner energy transitions in China - Ran Hao; Xin Sun; Yuchen Zhao; Jiahang Shang; Xue Zhu; Hongwei Li; Fengling Liu (Journal of Cleaner Production, 2025)

Transcriptome Analysis Reveals Hyperglycemic Hormone and Excitatory Amino Acid Transporter 3 Are Involved in the Thermal Adaptation of Eriocheir sinensis - Xi Li; Runlin Zhou; Ruiqi Zhang; Zhen He; Mingzhi Zhang; Ran Li; Tong Hao; Jinsheng Sun (Fishes, 2025)
Temperature is one of the critical factors influencing the survival, growth, and reproduction of organisms. The molting and developmental mechanisms of crustaceans are highly sensitive to temperature, yet the regulatory mechanisms underlying their thermal adaptation remain unclear. In this work, transcriptome sequencing was performed to analyze the gene expression profiles of Eriocheir sinensis under normal temperature (22 °C) and high-temperature (27 °C and 32 °C) conditions. A total of 377 differentially expressed genes (DEGs) were identified, including 149 up-regulated and 227 down-regulated genes. Through Gene Ontology (GO) enrichment analysis of these DEGs, 11 significantly temperature-regulated signaling pathways were identified, including the estrogen and androgen receptor signaling pathways, and two neurotransmission signaling pathways. These findings suggest that temperature may influence sex regulation in E. sinensis, while the dopamine receptor and neuropeptide signaling pathways may play a role in its thermal adaptation. Further validation via RT-qPCR of DEGs involved in neurotransmission signaling pathways revealed that crustacean hyperglycemic hormone (CHH) and excitatory amino acid transporter 3 (EAA3) genes are likely involved in the thermal adaptation of E. sinensis. In addition, the hemolymph glucose levels associated with the elevated temperatures were detected and consistent variations between glucose levels and CHH expressions were found. This indicates that the eyestalk CHH is strongly correlated with the hemolymph glucose levels and likely mediates the response to temperature changes by regulating blood glucose in E. sinensis. The results of this study not only provide key molecular targets for elucidating the mechanisms by which temperature affects molting and development in E. sinensis, but also establish a theoretical foundation for further research into thermal adaptation strategies in crustaceans.

Optimizing push-flow aeration in urban shallow lakes: Threshold-based algal control and nutrient dynamics through field-validated numerical modeling - Xin Sun; Jiahang Shang; Lihao Zhao; Hongwei Li; Ran Hao (Journal of Water Process Engineering, 2025)

Gradient layer arrangement for modulating the buried interface of inverted perovskite solar cells - Wenjing Miao; Ran Yin; Rongfei Wu; Weiwei Sun; Yansheng Sun; Kexiang Wang; Tingting You; Weichang Hao; Penggang Yin (Chemical Engineering Journal, 2025)

Glycosidase inhibitory isoflavones from the seeds of Cullen corylifolium and their structure–activity relationship study - Ying-Xiao Xiao; Yi-Ran Jiang; Wen-Hui Xu; Yuan Gao; Tian-Tian Bei; Hao Xu; Xue-Feng Wu; Hyun-Sun Lee; Long Cui (Natural Product Research, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Cellular mechanism of polarized auxin transport on fruit shape determination revealed by time-lapse live imaging - Yao Zhang; Hao-Ran Sun; Zhi-Cheng Hu; Yang Dong (Plant Reproduction, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Apatite geochemical indicators for magma mixing and fractional crystallization in the origin of A-type granite - Bao-Quan Zhou; Jin-Hui Yang; Jin-Feng Sun; Hao Wang; Yu-Sheng Zhu; Ya-Dong Wu; Qing-Feng Mei; Lei Xu; Jing Ran (Lithos, 2025)

Study on the degradation performance of coking wastewater using an in-situ enhanced Fe2+/Fe3+ cycle dual-cathode Electro-Fenton system - Chengwang Zhao; Yufang Ran; Yao Gong; Chen Hong; Yi Xing; Yunxiao Sun; Hao Wang; Wei Ling; Yijie Wang; Weibo Feng; Jiachen Hou; Xinlin Zhai; et al. (Journal of Environmental Chemical Engineering, 2024)

Comparative transcriptomic insights into key genes for biomass production and lipid synthesis in Chlorella sorokiniana mutated by argon and air atmospheric and room temperature plasma at different culture stages: Common mechanisms and unique differences - Hongwei Li; Xin Sun; Wei Li; Lei Ye; Xiaoxiao Sun; Ran Hao; Xiaoli Guo (Journal of Cleaner Production, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Silicon promotes biomass accumulation in Phragmites australis under waterlogged conditions in coastal wetland - Yuntao Wu; Xiaodong Zhang; Jiayang Lin; Xia Wang; Shaobo Sun; Qian Hao; Lele Wu; Jingyun Zhou; Shaopan Xia; Xiangbing Ran; Yidong Wang; Jiahuan Tang; et al. (Plant and Soil, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Effects of Tetraselmis subcordiformis (Wille) Butcher with antimicrobial peptides as feed additives on gut microbial community and immunity of turbot (Scophthalmus maximus L.) - Bingkui Zhu; Fengjie Sun; Zhengquan Gao; Ting Yao; Subing Han; Hao Zhang; Yuyang Ma; Yuyong Wu; Ran Du; Chunxiao Meng; Yulin Cui (Journal of Applied Phycology, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

From lab to nature: Overcoming challenges in applying in-situ photocatalysis to water bodies - Hao-Qin Xiong; Hao-Ran Bao; Fei Long; Yan-Yun Du; Jia-Zhuo Qu; Zhe-Xi Luan; Xiao-Long Sun (Journal of Environmental Chemical Engineering, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Three episodes of Triassic volcanism in the Eastern Kunlun Orogen, NW China: constraints for evolution of the Palaeo-Tethys Ocean - Hao-Ran Li; Jian-Feng Qiao; Feng-Yue Sun; Ye Qian; Yan-Zhang Wang; Shahzad Bakht; Hao-Tian Liu; Yan Gu (International Geology Review, 2024)

Excellent energy storage performance of lead-based antiferroelectric ceramics via enhancing dielectric breakdown mechanism - Jian Zhou; Zisheng Xu; Huilin Yang; Limin Chu; Liming Chen; Hangren Li; Jianxiang Ding; Songlin Ran; Zhengming Sun; Xihong Hao (Chemical Engineering Journal, 2024)

Experimental and numerical study on shear behaviour of concrete-filled double-skin steel tubular structures - Ran Ding; Hao-hao Bai; Yun-lun Sun; Yan Chen; Jian-sheng Fan (Engineering Structures, 2024)

Silicon fractionations in coastal wetland sediments: Implications for biogeochemical silicon cycling - Xiangwei Zhao; Zhaoliang Song; Lukas Van Zwieten; Yidong Wang; Xiangbin Ran; Qian Hao; Juqin Zhang; Zimin Li; Jun Sun; Yuqiu Wei; Lele Wu; Shuyan Liu; et al. (Science of The Total Environment, 2024)

Complexities of regulating climate by promoting marine primary production with ocean iron fertilization - Hai-Bo Jiang; David A. Hutchins; Hao-Ran Zhang; Yuan-Yuan Feng; Rui-Feng Zhang; Wei-Wei Sun; Wentao Ma; Yan Bai; Mark Wells; Ding He; Nianzhi Jiao; Yuntao Wang; et al. (Earth-Science Reviews, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

A spectral-temporal constrained deep learning method for tree species mapping of plantation forests using time series Sentinel-2 imagery - Zehua Huang; Liheng Zhong; Feng Zhao; Jin Wu; Hao Tang; Zhengang Lv; Binyuan Xu; Longfei Zhou; Rui Sun; Ran Meng (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Airborne PM2.5 pollution: A double-edged sword modulating hepatic lipid metabolism in middle-aged male mice - Renjie Hu; Lu Zhang; Li Qin; Hao Ding; Ran Li; Weijia Gu; Rucheng Chen; Yunhui Zhang; Sanjay Rajagoplan; Kezhong Zhang; Qinghua Sun; Cuiqing Liu (Environmental Pollution, 2023)

Time to reconsider the enigmatic tail of eastern Paleo-Tethys: New insights from Borneo - Xiao Ran Zhang; Sun-Lin Chung; Azman A. Ghani; Rezal Rahmat; Yi-Ju Hsin; Hao-Yang Lee; Ping-Ping Liu; Jinyu Xi (Lithos, 2023)

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Triptolide exposure induces oxidative stress and decreases oocyte quality in mouse - Qian-Qian Hao; Zhi-Ran Xu; Han Nie; Feng-Xin Qiao; Ming-Xin Sun; Yue-Cen Liu; Hai-Long Wang; Zhong-Quan Qi; Chang-Long Xu; Yu Liu (Toxicon, 2023)

Strengthening ion uptake and mitigating volume change via bimetallic telluride heterojunction for ultrastable K-ion hybrid capacitors - Zhihan Zeng; Wenqi Zhang; Hao Ma; Yuyang Yi; Xueyu Lian; Xianzhong Yang; Ran Cai; Wen Zhao; Jingyu Sun (Chemical Engineering Journal, 2023)

Prenylaromadendrane-type diterpenoids from the gum resin of Boswellia sacra flueck and their cytotoxic effects - Jia-Jia Wang; Xin-Yue Suo; Hao-Ran Sun; Xue Wang; Ming-Bao Lin; Jin-Hua Wang; Jian-Dong Jiang; Teng-Fei Ji (Natural Product Research, 2022)

Screening for SH3TC2 variants in Charcot–Marie–Tooth disease in a cohort of Chinese patients - Bo Sun; Zheng-Qing He; Yan-Ran Li; Jiong-Ming Bai; Hao-Ran Wang; Hong-Fen Wang; Fang Cui; Fei Yang; Xu-Sheng Huang (Acta Neurologica Belgica, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

A Highly Selective Turn‐on Fluorescent and Naked‐eye Colourimetric Dual‐channel Probe for Cyanide Anions Detection in Water Samples - Ya Wu; Wen-Min Ding; Juan Li; Geng Guo; Shu-Zhen Zhang; Hao-Ran Jia; Yin-Xia Sun (Journal of Fluorescence, 2021)

Innovative health risk assessments of heavy metals based on bioaccessibility due to the consumption of traditional animal medicines - Tian-Tian Zuo; Hao-Ran Qu; Hong-Yu Jin; Lei Zhang; Fei-Ya Luo; Kun-Zi Yu; Fei Gao; Qi Wang; Lei Sun; Huai-Zhen He; Shuang-Cheng Ma (Environmental Science and Pollution Research, 2020)

AUV 3D Path Planning Based on the Improved Hierarchical Deep Q Network - Yushan Sun; Xiangrui Ran; Guocheng Zhang; Hao Xu; Xiangbin Wang (Journal of Marine Science and Engineering, 2020)
This study proposed the 3D path planning of an autonomous underwater vehicle (AUV) by using the hierarchical deep Q network (HDQN) combined with the prioritized experience replay. The path planning task was divided into three layers, which realized the dimensionality reduction of state space and solved the problem of dimension disaster. An artificial potential field was used to design the positive rewards of the algorithm to shorten the training time. According to the different requirements of the task, this study modified the rewards in the training process to obtain different paths. The path planning simulation and field tests were carried out. The results of the tests corroborated that the training time of the proposed method was shorter than that of the traditional method. The path obtained by simulation training was proved to be safe and effective.

Three-Dimensional Path Tracking Control of Autonomous Underwater Vehicle Based on Deep Reinforcement Learning - Yushan Sun; Chenming Zhang; Guocheng Zhang; Hao Xu; Xiangrui Ran (Journal of Marine Science and Engineering, 2019)
In this paper, the three-dimensional (3D) path tracking control of an autonomous underwater vehicle (AUV) under the action of sea currents was researched. A novel reward function was proposed to improve learning ability and a disturbance observer was developed to observe the disturbance caused by currents. Based on existing models, the dynamic and kinematic models of the AUV were established. Deep Deterministic Policy Gradient, a deep reinforcement learning, was employed for designing the path tracking controller. Compared with the backstepping sliding mode controller, the controller proposed in this article showed excellent performance, at least in the particular study developed in this article. The improved reward function and the disturbance observer were also found to work well with improving path tracking performance.

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)